1 mei bijeenkomst 1981 Ahoy Rotterdam. V.l.n.r. Heyne den Bak, Van den Heuvel, Joop den Uyl, Liesbeth den Uyl, Van Kemenade - Morelis, Nick (1981)
1 mei bijeenkomst 1981 Ahoy Rotterdam. V.l.n.r. Heyne den Bak, Van den Heuvel, Joop den Uyl, Liesbeth den Uyl, Van Kemenade.